Caregivers' Attitudes Toward COVID-19 Vaccination in Children and Adolescents With a History of SARS-CoV-2 Infection - Danilo Buonsenso; Danilo Buonsenso; Piero Valentini; Piero Valentini; Marina Macchi; Francesco Folino; Carola Pensabene; Maria Francesca Patria; Carlo Agostoni; Carlo Agostoni; Silvana Castaldi; Silvana Castaldi; et al. (Frontiers Media S.A., 2022)
BackgroundLimited data are available on the attitudes of caregivers toward COVID-19 vaccination in children and adolescents with a history of SARS-CoV-2 infection or Long Covid symptoms. The aim of this study was to investigate the vaccine hesitancy among caregivers of children and adolescents with a documented history of SARS-CoV-2 infection and to explore the possible associations between COVID-19 manifestations and the acceptance of the vaccine.MethodsCaregivers of children or adolescents with a microbiologically confirmed diagnosis of SARS-CoV-2 infection evaluated in two University Hospitals were interviewed.ResultsWe were able to contact 132 caregivers and 9 declined to participate. 68 caregivers (56%) were in favor of COVID-19 vaccination for their child. In the multiple logistic regression, child's age (OR 1.17, 95%CI 1.06-1.28) and hospitalization due to COVID-19 (OR 3.25, 95%CI 1.06-9.95) were positively associated with being in favor of COVID-19 vaccination. On the contrary, the occurrence of child's Long Covid was associated with a higher likelihood of being against the vaccination (OR 0.28, 95%CI 0.10-0.80).ConclusionsThis preliminary study shows that only about half of the interviewed parents of children and adolescents with a previous SARS-CoV-2 infection are willing to vaccinate them to prevent a repeated COVID-19 infection. These findings might help healthcare workers to provide tailored information to caregivers of children with a previous SARS-CoV-2 infection.